Detecção de FIV e FeLV em felídeos domésticos e silvestres naturalmente infectados e avaliação da metodologia de diagnóstico - Silva, Carla Patricia Amarante e (2016)
The retroviruses are important viral diseases that affect domestic and non-domestic felines, among them are the feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV). The aims of this study were to investigate the occurrence of FIV and FeLV in domestic cats (Felis catus) in the Baixada Cuiabana and free-ranging jaguars (Panthera onca) in the Pantanal region of Mato Grosso, evaluate the diagnostic techniques (sorology and PCR) and involve the possible risk factors associated with infection in naturally infected felines. 164 samples of cats were analyzed in 21 samples of jaguars comparing the serologic techniques, PCR proviral DNA detection. The occurrence for FIV in cats was 11,58% (19/164) in serology and PCR 9,75% (16/164) and the FeLV serology results were 3,65% (6/164) and 12,19% (20/164) for PCR. Statistical analysis showed a significant association of gender (p = 0,02) oddis ratio 0,30 (I.C. 95%: 0,082- 0,967) with the positive serology for FIV in domestic cats and PCR (p = 0,03) oddis ratio 0,29 (I.C. 95%: 0,065- 1,024), and significantly associated with positivity in PCR for FeLV and socializing with other animals (p = 0,01) oddis ratio 0,12 (I.C. 95%: 0,002-0,806). The free-ranging jaguars were positive 01 (4,76%) in the PCR of blood to FeLV. The detection of FeLV in the wild Felidae population, specifically in a free-ranging jaguar in the Pantanal, has not been previously reported. This study showed for the first time a molecular diagnosis of the occurrence of FeLV in a free-ranging jaguar in the Pantanal wetland of Brazil. The PCR proved to be a test that can be used as a useful tool in the diagnosis for both FIV and for FeLV in felidae.